Les doléances en prothèse dentaire : un discours au prisme de la théorie de l’énonciation - Mokhtar Boughanem (Multilinguales)
The enunciative paradigm offers a relevant theoretical perspective for the apprehension of subjectivity in discourse. The passing from language to speech implies the intervention of a speaker whose role is to mobilize "the formal apparatus of enunciation". The positioning of the speaker is then manifested through linguistic indicators that form a deictic and modal tracking system.Starting from this theoretical framework, this article proposes to deal with the enunciative functioning of the complaints following the wearing of dental prostheses. The subject wearing dental prothesis stands as a speaker for whom the language serves to express his feeling towards the treatments that have been made to him. The analysis proposed in this context is intended to be qualitative in that it aims to identify the enunciative regularities inherent to post-prosthetic complaints.